Perceptions, conservation orientations, and socio-geographical determinants of bamboo ecosystem services: evidence from Taiwan - Li, Chong-En; Hsu, Cheng-Mao; Yuan, Mei-Hua (Frontiers in Ecology and Evolution, 2025)
Although bamboo forests provide critical ecosystem services that support human well-being, public perceptions and conservation orientations regarding these contributions remain underexplored. Existing research has predominantly examined small rural communities in the Global South, limiting insights into how bamboo is valued in other contexts. This study addresses this gap by (1) assessing residents’ perceptions of bamboo ecosystem services in a newly industrialized economy (i.e., Taiwan); (2) evaluating their conservation orientations toward different management strategies and willingness to pay; and (3) analyzing how socioeconomic and geographical factors determine these views. We conducted a questionnaire survey with 400 valid respondents, using stratified sampling to capture diverse backgrounds. The data were subsequently analyzed through descriptive statistics, ANOVA, and hierarchical logistic regression. The results indicate that leisure and eco-tourism scored the highest at 4.02 on a 5-point scale, while healthy food and handicrafts were the most recognized benefits of bamboo. These findings reflect respondents’ preference for ecosystem services that enhance quality of life. However, although respondents acknowledge the importance of proactive conservation, only 29.3% expressed a willingness to pay, with a modal value of TWD 1,000 per year. Notably, collective-oriented environmental attitudes significantly influence respondents’ willingness to pay for bamboo conservation. These results extend the literature by demonstrating how the subjective meanings and values of bamboo ecosystem services shift as economies industrialize. We further derived policy recommendations for adaptive management reflecting residents’ non-market valuations of bamboo and emphasizing rapid, visible actions to secure public support. Enhancing financial transparency, linking personal contributions to outcomes, and developing incentive-based payment models are likely to increase willingness to pay.